2009
DOI: 10.1007/s10552-009-9466-0
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D association with estradiol and progesterone in young women

Abstract: Higher levels of vitamin D may reduce progesterone and estradiol, providing a potential mechanism for reduction in breast cancer risk from increased vitamin D exposure in young women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 16 publications
3
40
1
3
Order By: Relevance
“…In particular, we adjusted for the effect of seasonal and latitude effects on 25(OH)D3 synthesis via the date, the center, or the mean daily UV dose for the center at the time of blood collection; in addition, we adjusted for calcium and PTH serum concentrations. We also took into account estradiol and progesterone serum concentrations, which have been reported to be associated with vitamin D status (12,26). Moreover, we controlled for both dietary and supplement intakes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we adjusted for the effect of seasonal and latitude effects on 25(OH)D3 synthesis via the date, the center, or the mean daily UV dose for the center at the time of blood collection; in addition, we adjusted for calcium and PTH serum concentrations. We also took into account estradiol and progesterone serum concentrations, which have been reported to be associated with vitamin D status (12,26). Moreover, we controlled for both dietary and supplement intakes.…”
Section: Discussionmentioning
confidence: 99%
“…Among six case-control studies nested in cohorts, only a recent study (20) found a statistically significant inverse association, whereas the others failed to find any association (21)(22)(23)(24)(25). Studies which analyzed data by menopausal status (14,15,17,(20)(21)(22)(23)(24)(25) or age (19,22) suggested that the effect of vitamin D on breast cancer is modulated by the hormonal milieu, a suggestion further supported by the recent finding of an association between circulating 25(OH)D and steroid hormones in young women (26).…”
Section: Introductionmentioning
confidence: 94%
“…Serum level of estrogen and progesterone in young women was shown to be inversely related with serum 25-OHD levels [35].…”
Section: Discussionmentioning
confidence: 95%
“…[81] Decreasing vitamin D 3 levels and increasing ROS with advancing age along with male estrogen levels that are 2-3 times higher than females over the age of 49 might explain why all cancer incidences increase with increasing age and steadily increase with advancing age of males (see Figures 3A and 3B and values in Table 3). Intriguingly, lower levels of vitamin D lead to higher levels of estrogen in a dose dependent manner, [82] so that estrogen might have actually been slowly increasing over recent decades in only developed countries where most people work indoors. Lower cancer incidences in Asians and other populations compared to European populations might be from outdoor work leading to good vitamin D 3 levels and the fact that they primarily synthesize eumelanin (black hair), which absorbs ROS, rather than pheomelanin (red and blond hair) that produces ROS, so that ROS do not activate HPV and cause increased release of its virions.…”
Section: Discussionmentioning
confidence: 99%